A Comparison Study on Relationship Between Welding Current and Penetration for Plasma Enhanced Shielded Metal Arc Welding(PESMAW). - S.THIRU,, CHITRAMBALAM; S.HEMA,, VATHI; AHMAD, RIVAI; PANDEY, SUNIL (2011)
For open root pass girth welds, manual welding with cellulosic electrodes is still the most widely used process in spite of its susceptibility to hydrogen-induced defects. Barring considerable losses due to productiondelays and failures, the pipeline industry has learnt to live with these defects, as cellulosic electrodes are capable of producing low cost, high penetration welds- a prerequisite for pipe welding. Nevertheless, attempts have been made by researchers to reduce hydrogen levels in pipeline weldments either by altering the procedure techniques or by adopting different processes or by introducing new fabrication materials and methods. The Plasma Enhanced Shielded Metal Arc Welding (PESMAW), a modified version of the conventional Shielded Metal Arc Welding (SMAW) is one among these attempts, aimed to amplify penetration levels in general-purpose, rutile-coated electrodes at comparatively lower currents. It employs gas carrying tubular covered electrodes with a specially designed Universal Electrode Holder (UEH), which has provisions for external gas supply through the orifice of the electrodes. The gas introduced at the tip of the electrode gets ionized in the arc column and develops auxiliary plasma. This enhances the heat content of the weldment and yields high penetration weld beads at low currents. This paper presents an investigation on the performance of PESMAW by applying it to the welding of mild steel sheet of thickness 5 mm. The effect of welding current on bead geometry & shape relationships of welds, micro hardness analysis andweld microstructure were studied. Flat position ‘bead on plate’ technique was used to deposit weld beads in a mechanized manner. CO2 was used as the orifice gas through the general-purpose rutile coated tubular electrodes. It was observed that the flow of orifice gas during welding resulted in the increase in weld penetration, while the absence of plasma gas resulted in flatter and wider weld beads.